Gly197Arg mutation in protein C causes recurrent thrombosis in a heterozygous carrier. (9th April 2020) - Lu, Yeling; Giri, Hemant; Villoutreix, Bruno O.; Ding, Qiulan; Wang, Xuefeng; Rezaie, Alireza R.
Abstract: Background: Activated protein C (APC) downregulates thrombin generation by inactivating procoagulant cofactors Va and VIIIa by limited proteolysis. We identified two protein C‐deficient patients both of whom carry a heterozygous Gly197 to Arg (G197R) mutation in PROC and experience venous thrombosis. Objective: The objective of this study was to determine the molecular basis of the clotting defect in patients carrying the G197R mutation. Methods: We expressed protein C‐G197R in mammalian cells and characterized its properties in established coagulation and anti‐inflammatory assay systems. Results: The activation of protein C‐G197R by thrombin was improved ~10‐fold; however, its activation by thrombin was not promoted by thrombomodulin (TM). In a tissue factor‐mediated thrombin generation assay, the addition of soluble TM to protein C‐deficient plasma, supplemented with protein C‐G197R, did not have a significant inhibitory effect on thrombin generation parameters. APC‐G197R did not exhibit a significant anticoagulant activity in either purified or plasma‐based assay systems. APC‐G197R was essentially inactive because it showed no activity in an aPTT assay. Anti‐inflammatory activity of APC‐G197R was also dramatically impaired as determined by an endothelial cell permeability assay. Structural modeling predicted that the side‐chain of Arg cannot be accommodated at this site of APC without a major distortion of the local structure that appears to propagate and adversely affect the reactivity/folding of the catalytic pocket. Conclusion: The G197R mutation in patients appears to be functionally equivalent to a heterozygous protein C knockout with half of the protein having no significant activity and thus causing thrombosis.